PENGARUH SHIFT KERJA TERHADAP KELELAHAN PEKERJA PABRIK SAWIT DI PTPN V SEI GALUH - Syafril Syafar; Aris Fiatno (Jurnal Teknik Industri Terintegrasi, 2018)
Workers who work the night shift have a tendency to get stressed and subsequently suffer from fatigue as a clinical symptom. This study aims to formulate an effective strategy of policy to emphasize the reduction in the effect of applying work shifts to the risk of fatigue. Based on the results that the average amount of reactive time for morning shift workers is 0.97 seconds, while for night shift workers is 1.18 seconds. The average amount of blood systole pressure for morning shift workers is 119.22 cm Hg, while for night shift workers is Hg 127.61 cm. The average amount of blood diastole pressure for morning shift workers was 77.44 cm Hg, while for night shift workers it was 82.16 cm Hg. The average heart rate for morning shift workers was 73.93, while for night shift workers it was 76.18. Based on the results of a statistical examination that there is a significant effect on fatigue (p = 0,000), it means that there is a significant relationship between work shifts and stress-causing fatigue (p = 0,000). Therefore, as the proposal of this study and to anticipate the reduction in fatigue, it is important to make improvements and evaluations about the rules of work shifts in a company so that night shift workers can work in safe conditions and rest well after work